Tax competition - Von Haldenwang, Christian; Faccio, Tommaso; Hentze, Tobias; Mättig, Thomas; Valderrama, Irma Johanna Mosquera; Redonda, Agustín; Rigoni, Gabriela; Schwab, Jakob; Vos, Rob (T20 Argentina, 2018)
The world is facing a new round of international tax competition that may result in a ruinous race to the bottom, undermining the fiscal capacity of states to respond to global challenges and to implement the Agenda 2030. G20 leaders must take action to strengthen multilateral and cooperative approaches to taxation, curtail harmful tax competition and protect their own tax base as well as that of developing countries.